Trend analysis of green turtle (Chelonia mydas) and hawksbill turtle (Eretmochelys imbricata) landings in Paloh District, West Kalimantan - Jakaria Mohamad; Dikari Kusrini Mirza; Mukhlis Kamal Mohammad (BIO Web of Conferences)
Kalimantan sea turtles are considered conservation icons due to their crucial role in maintaining marine ecosystem balance and serving as indicators of global water conditions. However, their population in Paloh District, West Kalimantan, is increasingly threatened by habitat destruction, human activities, and the illegal trade of turtle eggs. This study aims to provide data on the region's landing population trends of different sea turtle species. Data collection on nesting turtles was conducted by direct survey and information from the West Kalimantan Natural Resources Conservation Center and the Wahana Bahari Community Monitoring Group. The monitoring focused on the Tanjung Belimbing Nature Park coastlines, Sungai Belacan, and Tanjung Api Beach from 2008 to 2023. The findings reveal significant variations in the number of landing turtles, with a declining trend in the populations of Green Turtles and Hawksbill Turtles at the monitored sites.